Analisis Kemampuan Pemecahan Masalah Peserta Didik pada Materi Sistem Persamaan Dua Variabel (SPLDV) ditinjau dari Self-Efficacy - Syam, Lisa Kurnia; Jabbar, Fitriani; Suardi, Achmad Fauzan; Angriani, Andi Dian; Nursalam, Nursalam; Sulasteri, Sri; Baharuddin, Baharuddin; Halimah, Andi (Al Asma: Journal of Islamic Education, 2025)
Problem-solving is a fundamental mathematical skill that serves as both the primary goal and the core of mathematics education. Problem-solving is often presented in the form of word problems, including those found in the topic of systems of linear equations in two variables (SPLDV). Self-efficacy is one of the many factors that influence students' problem-solving abilities. This study aims to describe the problem-solving abilities of junior high school students based on their self-efficacy levels. This research is a qualitative descriptive study. The subjects were three eighth-grade students from MTsN 1 Bone. The primary instrument used in this study was the researcher, supported by interview guidelines and a problem-solving test on the SPLDV material. The findings revealed that high-ability students were able to plan and implement strategies to solve problems effectively, while students with moderate and low abilities lacked accuracy in solving problems. All three students demonstrated a reasonably good level of self-confidence in solving the given problems, utilized their learning experiences in the process, and had a positive outlook on the results obtained. The implication of this study suggests that strengthening students' self-efficacy can be an effective strategy for improving mathematical problem-solving skills, particularly in the topic of SPLDV.